A fast information scheduling algorithm for large scale logistics supply chain. (3rd October 2017) - Changan, Ren; Zhao, Jinguo; Chen, Liping
Abstract: At present, large-scale logistics supply chain information is quickly dispatched, too many constraints are existed. Therefore, a fast information scheduling algorithm for large-scale logistics supply chain based on adaptive genetic optimization is proposed in this paper. The genetic algorithm is used to get the solution and the adaptive technology is brought to solve the congestion problem of genetic algorithm. Experiments show that the proposed algorithm can effectively improve the efficiency of scheduling and solve the existing problems.